Upstanding Youngsters: Ivorian Scouting and the Manufacture of a Subordinate Citizenship (1937–1979) - Nicolas, Claire (Frontiers in Sports and Active Living, 2020)
This research focuses on Ivoirian scouting from its colonial implementation in the late 1930s up to the late 1970s, under Félix Houphouet-Boigny’s regime. Using a novel perspective, it highlights the gender lines of scouting youth training in West Africa. Furthermore, this paper argues that understanding this history of Ivoirian youth through the lens of the scouting movement allows us to articulate youth governance between the colonial and postcolonial era, notably in order to understand the political and moral subordination of Ivoirian youth during the 20th century. This research is based on archives collected in France, Côte d’Ivoire and Switzerland as well as biographical interviews conducted in 2016.